Adaptation responses to salt stress in the gut of Poecilia reticulata - Hyerim Lee; Hyunjae Yeo; Jihye Park; Keunsoo Kang; Sun-Ju Yi; Kyunghwan Kim (Animal Cells and Systems)
Osmoregulation is essential for the survival of aquatic organisms, particularly teleost fish facing osmotic challenges in environments characterized by variable salinity. While the gills are known for ion exchange, the intestine’s role in water and salt absorption is gaining attention. Here, we investigated the adaptive responses of the intestine to salinity stress in guppies (Poecilia reticulata), observing significant morphological and transcriptomic alterations. Guppies showed superior salt tolerance compared to zebrafish (Danio rerio). Increasing salinity reduced villus length and intestinal diameter in guppies, while zebrafish exhibited damage to villus structure and loss of goblet cells. Transcriptomic analysis identified key genes involved in osmoregulation, tissue remodeling, and immune modulation. Upregulated genes included the solute carrier transporters slc2al and slc3al, which facilitate ion and water transport, as well as a transcription factor AP-1 subunit and phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit beta, both of which participate in tissue repair and growth responses. In contrast, many genes related to the innate immune system (such as Tnfaip6) were downregulated, suggesting a shift toward the prioritization of osmoregulatory functions over immune responses. Interestingly, the differential expression of adaptation genes was linked to variations in epigenetic modifications and transcription factor activity. Transcription factors crucial for adapting to salt stress, such as bhlhe40, cebpd, and gata6, were progressively upregulated in guppies but remained downregulated in zebrafish. Our findings highlight the intricate mechanisms of adaptation to salinity stress in P. reticulata, providing insights into osmoregulatory mechanisms involving the intestine in aquatic organisms.